Interior Design of Samin Community Culture Museum With Neo Vernacular Concept in Blora - Rahmanu Widayat; Fadhilla Novrizka, Dzia (TAMA: Journal of Visual Arts, 2023)
Samin Community Tourism Village in Blora is located in the middle of the forest and also far from the hustle and bustle of the city, as well as a place to store cultural heritage from the Samin culture is also very less a problem experienced by the Samin Community Tourism Village. Not many people in general know about the Samin people who live in the Klopo Dhuwur Village area, Blora. Therefore, to introduce and preserve the culture of the Samin people, a place that can maintain the collections of the Samin people's heritage is needed. Samin Community Cultural Museum was designed with a neo vernacular concept in which this concept combines modern and traditional concepts in its interior. This concept was chosen to design a museum that is interactive but does not leave the culture of the surrounding area. The neo vernacular concept will be implemented in interior elements and furniture.